Neuroanesthesia Management in Pediatric with Traumatic Brain Injury in Emergency Operation - Fitri Hapsari Dewi; Achmed Rizal Fatahillah (Faculty of Medicine, Brawijaya University, 2022)
Background: Pediatric neuroanaesthesia is an exciting and challenging branch of anaesthesia. Because the anatomy and physiology of the neurological system of children are still immature, the management of neuroanaesthesia in children is different from that of adults, from hemodynamic control, selection of anaesthetic drugs used, to endotracheal intubation.Case: In this case report, we report a 1-month-old male infant, weighing 4.6 kg, with a diagnosis of acute on chronic SDH in the frontotemporoparietal region. Physical examination revealed a decrease in consciousness GCS E2V2M5, with a pulse of 157 times per minute, a respiratory rate of 48 times per minute and a 100% SpO2 with oxygen administration of 2 litres per minute through a nasal cannula. On examination of the airway, there was no gurgling, snoring, or hoarseness. The patient was hemodynamically stable during the 90-minute operation. Postoperatively the patient was admitted to the PICU.Conclusion: Anaesthesia treatment for traumatic brain injury in infants has unique problems that require knowledge of the anatomy and physiology of the pediatric brain. Keywords: frontotemporoparietal region, neuroanaesthesia, paediatrics, traumatic brain injury